Base-Promoted [3+2] Annulation of Carbodiimides with Diazoacetonitrile for Synthesis of 5-Amino-4-cyano-1,2,3-triazoles - Zhou, Lu-Nan; Zhang, Fa-Guang; Cheung, Chi Wai; Ma, Jun-An (Synlett, 2024)
1,2,3-Triazoles are a privileged class of heterocycles in medicinal and agrochemical science. Here, we describe the base-promoted [3+2] annulation of carbodiimides with diazoacetonitrile. This reaction protocol permits access to a variety of novel 5-amino-4-cyano-1,2,3-triazoles in a regiospecific manner. Further derivatization is exemplified by a skeletal rearrangement and an N-functionalization of triazole products.
Keywords: annulation; triazoles; [3+2] annulation; carbodiimides; diazoacetonitrile